A Good Way to Reduce Screening for Retinopathy of Prematurity: Development of the ROP Model in a China Preterm Population - Ding, Wenqian; Luo, Chenghan; Cheng, Xinru; Shi, Zanyang; Lei, Mengyuan; Rong, Junbo; Song, Min; Cao, Wenjun; Zhang, Jingdi; Ge, Jian; Wang, Mengmeng; Zhang, Yixia; et al. (Frontiers in Pediatrics, 2021)
Importance: Retinopathy of prematurity (ROP) is a preventable cause of blindness in children. Without treatment, more than 45 percent of eyes may suffer permanent vision loss. Current ROP screening guidelines, which include a range of birth weight (BW) and gestational age (GA), may require screening for many low-risk preemies who develop severe ROP. Method：All high-risk infants in the neonatal intensive care unit (NICU) of the First Affiliated Hospital of Zhengzhou University from 2017 to 2021 were included in this retrospective cohort study. Each of the 27 candidate risk factors was evaluated in univariate analysis and adjusted for known risk factors (i.e., GA, BW). Significant results were analyzed in a backward selection multivariate logistic regression model.Receiver opreating characteristic curves(ROC) and the nomogram were drawn. Results: The study included 2040 infants who underwent ROP screening. Weight gain rate (OR, 2.65; 95% confidence interval (CI), 1.49-1.21≤12g/L vs >18g/L; P = .001), blood transfusion (OR, 2.03; 95%CI,1.14-3.64; P=.017), invasive mechanical ventilation(OR, 1.74; 95%CI,1.15-2.66; P=.009) and N-terminal segment of pro-B-type natriuretic peptide (NT-proBNP)≥25000ng/L (OR, 1.51; 95% CI, 1.00-2.28; P= .048) were four new statistically independent risk factors besides GA and BW. The area under curve (AUC) of the final multivariate model was 0.90(95%CI, 0.88-0.92; P< .001). Conclusions and Relevance: These findings add to our understanding of ROP screening because they include all eligible infants, rather than only high-risk infants, as in previous studies. Under the control of BW and GA, weight gain rate, blood transfusion, invasive mechanical ventilation and NT-proBNP≥25000ng/L were “new” statistically independent risk factors for ROP. ROP risk can be calculated manually or represented by nomogram for clinical use.